Treated sewage effluent as a source of water and nitrogen for Tifton 85 bermudagrass - da Fonseca, Adriel Ferreira; Melfi, Adolpho José; Monteiro, Francisco Antônio; Montes, Célia Regina; Almeida, Vagner Vidal de; Herpin, Uwe (Agricultural water management, 2007)
The use of treated sewage effluent in agriculture has been a current practice in several countries. However, in Brazil, there are few studies about this subject. This research work aimed at evaluating the potential utilization of secondary-treated sewage effluent (STSE) as an alternative source of water and nitrogen (N) for Tifton 85 bermudagrass pasture. A field experiment was carried out at Lins, State of São Paulo, Brazil, for 2 years, using a randomized complete block design, with four replications and five treatments, as follows: (i) T1 (control) – irrigation with potable water and addition of mineral-N fertilizer (MNF) – 520 kg N ha −1 year −1; (ii) T2–T5 – irrigation with STSE (31.9 mg total-N L −1) and addition of MNF – 0, 171.6, 343.2 and 520 kg N ha −1 year −1, respectively. Potable water and STSE characteristics were monitored monthly; above ground grass dry matter yield (DM) and crude protein content (CP) were determined bimonthly. Increases in DM and CP were observed for the high MNF rates associated with irrigation with STSE. STSE irrigation can efficiently substitute potable water for irrigation of Tifton 85 bermudagrass pasture and, simultaneously, save 32.2–81.0% of the recommended N rate without loss of grass DM and CP yield.